Uma primeira abordagem à cerâmica decorada do 4.º / 3.º milénio a.n.e. dos povoados de S. Pedro (Redondo) - Costeira, Catarina (2014)
This article is a first approach to the decorated pottery from the archaeological site of S. Pedro (Redondo, Central Alentejo), chronologically integrated in the 4th / 3th millennium BCE. In the Alentejo region, in the chronology under analysis, it is commonly accepted the rarity and simplicity of decorated pottery. However, the analyzed data are numerically more expressive and stylistically more diverse than expected. We intend to organize the techniques and decorative motifs in large groups and located them into spaces and phases of the S. Pedro’s site, as well as discuss major interpretive readings.